Methods and Stages of Ijtihad in Fiqh Nawazil: Correlation and Implementation in Fatwa of the Indonesia Ulama Council Related to Covid-19 - Ulil Albab, Muhammad; Nurwahidin, Nurwahidin (Alhurriyah, 2022)
Fiqh, like the law in general, always faces new problems (nawÄzil) that need solutions through ijtihad. To establish the law of the problem of fiqh nawazil,Â a standard method of ijtihad is needed. Through this research, the author seeks to review the literature related to ijtihad fiqh nawazilÂ to be assembled into a standard method, which is then compared with the procedure of establishing fatwa of the Indonesian Ulama Council (MUI) and used as a theory to dissect MUIÂ fatwaÂ related toÂ Covid-19.Â From the results of the study of related literature, ijtihad fiqh nawazilÂ can be conducted by three methods, namely bayÄnÄ«, taâ€™lÄ«lÄ«, and istiá¹£laá¸¥Ä«, which are then practiced through three stages, namely taá¹£awwur al-masalat,Â takyÄ«f fiqhÄ«,Â and taá¹bÄ«q al-ahkÄm.Â Although there is a slight differenceÂ inÂ the aspect of language between the methods and stages of theÂ ijtihad fiqh nawazil with the MUI fatwa establishment procedure,Â both have the same substance, so it can be concluded that the fatwa establishment procedure of the MUI has included three stages of the ijtihad fiqh nawazil methods. This is increasingly seen in the MUI fatwa decree related toÂ Covid-19,Â especiallyÂ inÂ the Law on the Use of AstraZeneca Vaccine.Fikih, sebagaimana hukum pada umumnya, akan selalu menemui masalah-masalah baru (nawÄzil) yang membutuhkan solusi melalui proses ijtihad. Untuk menentukan hukum dari masalah fikih nawÄzil, diperlukan metode ijtihad yang baku. Melalui penelitian ini, penulis berupaya mengkaji literatur-literatur yang berkaitan dengan ijtihad fikih nawÄzil untuk dapat dirangkai menjadi sebuah metode baku, yang kemudian dikomparasikan dengan prosedur penetapan fatwa Majelis Ulama Indonesia (MUI), serta digunakan sebagai teori untuk membedah fatwa-fatwa MUI terkait Covid-19. Dari hasil pengkajian literatur-literatur terkait, ijtihad fikih nawÄzil dapat dilakukan dengan tiga metode, yaitu bayÄnÄ«, taâ€™lÄ«lÄ«, dan istiá¹£laá¸¥Ä«, yang kemudian dipraktikkan melalui tiga tahapan, yaitu taá¹£awwur al-masalat, takyÄ«f fiqhÄ«, dan taá¹bÄ«q al-ahkÄm. Meskipun terdapat sedikit perbedaan dari aspek kebahasaan antara metode dan tahapan ijtihad fikih nawÄzil tersebut dengan prosedur penetapan fatwa MUI, keduanya memiliki substansi yang sama, sehingga dapat disimpulkan bahwa prosedur penetapan fatwa MUI telah mencakup tiga tahapan dari metode ijtihad fikih nawÄzil tersebut. Hal ini semakin terlihat implementasinya dalam Surat Keputusan Fatwa MUI terkait Covid-19, terkhusus tentang Hukum Penggunaan Vaksin Covid-19 Produk Astrazeneca.